Zollinger-Ellisonov sindrom - Krajnc, Mitja (Zdravniški vestnik, 2006)
Background. Zollinger-Ellison syndrome is the consequence of excessive and autonomous secretion of gastrin from gastrinoma cells. The disease is exceptionally rare and characterized by severe and treatment-resistant peptic disease that can become life-threatening for a patient. In most cases, gastrinoma is malignant. A case of 44-year patient is presented. Conclusions. We present clinical manifestations, laboratory diagnostic tests, modalities of tumor localization and forms of treatment that are clinically relevant in a patient, suspected of having this rare disease. Pathohistologically, our patient's tumor was identified as a carcinoid with minor gastrinoma fraction.
Keywords: diagnosis; Diagnosis, Differential; Diagnostika; Diferencialna diagnostika; Gastrinom; Gastrinoma; prebavila; therapy; Zdravljenje; Zollinger-Ellison Syndrome; Zollinger-Ellisonov sindrom